Metabolism of Caprine Milk Carbohydrates by Probiotic Bacteria and Caco-2:HT29⁻MTX Epithelial Co-Cultures and Their Impact on Intestinal Barrier Integrity - Barnett AM; Roy NC; Cookson AL; McNabb WC (MDPI (Basel, Switzerland), 2018)
The development and maturation of the neonatal intestine is generally influenced by diet and commensal bacteria, the composition of which, in turn, can be influenced by the diet. Colonisation of the neonatal intestine by probiotic Lactobacillus strains can strengthen, preserve, and improve barrier integrity, and adherence of probiotics to the intestinal epithelium can be influenced by the available carbon sources. The goal of the present study was to examine the role of probiotic lactobacilli strains alone or together with a carbohydrate fraction (CF) from caprine milk on barrier integrity of a co-culture model of the small intestinal epithelium. Barrier integrity (as measured by trans epithelial electrical resistance (TEER)), was enhanced by three bacteria/CF combinations (Lactobacillus rhamnosus HN001, L. plantarum 299v, and L. casei Shirota) to a greater extent than CF or bacteria alone. Levels of occludin mRNA were increased for all treatments compared to untreated co-cultures, and L. plantarum 299v in combination with CF had increased mRNA levels of MUC4, MUC2 and MUC5AC mucins and MUC4 protein abundance. These results indicate that three out of the four probiotic bacteria tested, in combination with CF, were able to elicit a greater increase in barrier integrity of a co-culture model of the small intestinal epithelium compared to that for either component alone. This study provides additional insight into the individual or combined roles of microbe⁻diet interactions in the small intestine and their beneficial contribution to the intestinal barrier.
Keywords: barrier integrity; caprine milk carbohydrates; in vitro studies; probiotic lactobacilli bacteria; small intestinal epithelium; Animals; Caco-2 Cells; Carbohydrate Metabolism; Carbohydrates; Coculture Techniques; Epithelial Cells; Goats; HT29 Cells; Humans; Lactobacillus; Milk; Probiotics; RNA, Messenger